PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA ORGANISASI BIPP KULON PROGO - Raya, Alia Bihrajihant; Wastutiningsih, Sri Peni; Widodo, Sri (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2007)
This research aims to identify the differences between organizational culture and organizational interrelationship between BIPP Kulon Progo and NGO; and the influence of organizational culture towards organizational performance of BIPP Kulon Progo. This research was conducted at BIPP Kulon Progo and NGO (Yabimas NGO and DAMARs NGO) in Kulon Progo Regency, Yogyakarta Province. The descriptive analytical and explanative method was used in this research. Two independent sample t-tests were used to identify the differences of organizational culture and organizational interrelationship between BIPP Kulon Progo and NGO. Then, multiple regression analysis was used to know the effects of organizational culture and organizational interrelationship on organizational performance of BIPP Kulon Progo.The results showed that organizational culture in NGO was stronger than BIPP Kulon Progo. The policies of organizational interrelationship were also different. BIPP Kulon Progo developed relationship rather than partnership. Therefore, partnership had no significant effect on organizational performances. In the other side, organizational culture and relationship had a positive effect on organizational performance of BIPP Kulon Progo.